Caracterización productiva mediante análisis de conglomerados de las principales variedades comerciales de poroto negro (Phaseolus vulgaris L.) en el noroeste argentino - Vizgarra, Oscar Nicéforo; Terán Santofimio, Henry; Toll Vera, Jorge R. (1998)
The objectives of the present work were productivity characterization of the six most widely black dry edible beans cultivars cropped in the NorthWest of Argentina according to Clusters Analysis and its comparison with Varietal Stability results obtained by Environmental Indexes. The experience was conducted at the localities of Taco Ralo, Monte Redondo (Tucumán) and Campichuelo (Salta) since 1994 to 1996. The experimental design was in Complete Randomized Blocks with 3 repetitions and environmental stability was measured using Eberhart and Rusell (1966) and Finlay and Wilkinson (1963) Methods. The varietal characterization by means of Clusters Analysis was establish using Ward`s minimum variances model (SAS, 1988). It was concluded that: 1.- Under the present study conditions, the Cluster Analysis was more precise than Lineal Regression and Environmental Stability Parameters in the differentiation of varietal behaviour of six most widely black dry edible beans cropped at NW of Argentina. 2- The cultivars TUC 390 and TUC 500 conformed a superior group in adaptative and productive capacity in the diverse studied environments. 3- DOR 157, BAT 304 and JEO constitute an intermedium production group with lower productive response under favourable considered environments, when compared with TUC 500 and TUC 390. 4- Cultivars DOR 157 and JEO were the most stable ones. 5- The cultivar NAG 12 exhibed the lowest environmental productive plasticity of all.